Retrospective Review of TURP Done in One Year and Report on Postoperative Outcome - Uddin, Md Mohsin; Amin, Ruhul; Rahman, Md Mostafizur; Chowdhury, Sirajum Monira; Khan, Md Rashed; Islam, Md Rashedul (KYAMC Journal, 2017)
To assess the short-term clinical outcome of transurethral resection of prostate (TURP) at Khwaja Yunus Ali Medical College & Hospital (KYAMCH).This is a retrospective study performed in the urology department of our hospital for a period of one year. For all patients conventional monopolar resection was performed. Glycine was used as irrigant. Usually patients were admitted 1 day before surgery. TURP was performed under spinal anesthesia. All patients received intravenous prophylactic antibiotic. In most patients we have removed indwelling catheter on 2nd postoperative day.In one year, we have performed 45 TURPs. The median age of the patient was 67.0(48-85) years. Most common indication was acute retention of urine (62.2%). Median prostatic volume was 52.3mls on transabdominal ultrasound. The median weight of resected prostatic tissue was 24.25gm (5-60 gms), with a median resection time of 63.5 min. There was no mortality. Five patients (11.1%) received blood transfusion during or immediate post operative period of TURP. No patient develop TURP syndrome, one patient developed post-TURP febrile UTI. No patient developed permanent incontinence in our study.TURP is safe and effective in reducing the symptoms and complications related to benign prostatic hyperplasia .Advances in techniques, instrumentation, surgical and perioperative management, careful selection of patients and early catheter removal policy might increase the efficiency of TURP with acceptable complication rates. KYAMC Journal Vol. 4, No.-1, July 2013, Page 321-325